Effects of an outdoor bicycle-based intervention in healthy rural Indian men with normal and low birth weight. (17th December 2014) - Madsen, C.; Mogensen, P.; Thomas, N.; Christensen, D. L.; Bygbjerg, I. C.; Mohan, V.; Inbakumari, M.; Nadig, S. V.; Alex, R.; Geetanjali, F. S.; Westgate, K.; Brage, S.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Physical inactivity and low birth weight (LBW) may lead to an increased risk for developing type 2 diabetes. The extent to which LBW individuals may benefit from physical exercise training when compared with those with normal birth weight (NBW) controls is uncertain. We assessed the impact of an outdoor exercise intervention on body composition, insulin secretion and action in young men born with LBW and NBW in rural India. A total of 61 LBW and 56 NBW healthy young men were recruited into the study. The individuals were instructed to perform outdoor bicycle exercise training for 45 min every day. Fasting blood samples, intravenous glucose tolerance tests and bioimpedance body composition assessment were carried out. Physical activity was measured using combined accelerometry and heart rate monitoring during the first and the last week of the intervention. Following the exercise intervention, the LBW group displayed an increase in physical fitness [55.0 ml (O2)/kg min (52.0−58.0)−57.5 ml (O2)/kg min (54.4−60.5)] level and total fat-free mass [10.9% (8.0−13.4)−11.4% (8.0−14.6)], as well as a corresponding decline in the ratio of total fat mass/fat-free mass. In contrast, an increase in total fat percentage as well as total fat mass was observed in the NBW group. After intervention, fasting plasma insulin levels, homoeostasis model assessments (HOMA) of insulin resistance (HOMA-IR) and insulin secretion (HOMA-IS), improved to the same extent in both the groups. In summary, young men born with LBW in rural India benefit metabolically from exercise training to an extent comparable with NBW controls.